A Critical Review of the Literature for Sales Educators. (April 2013) - Cummins, Shannon; Peltier, James W.; Erffmeyer, Robert; Whalen, Joel
The Journal of Marketing Education is publishing a special issue on Sales Education and Training in August 2014. In this article, we review the sales education literature from four primary journals and the business literature at large. The four primary journals are the Journal of Marketing Education, Marketing Education Review, Journal of Education in Business, and the Journal of Personal Selling & Sales Management . Of the 107 identified articles, experiential learning, assessment, and career development were the three most prominent topics. Future research opportunities in sales education, including those for the special issue, are offered across nine topical areas.